Effect of SiO₂ Nanoparticle Dispersion on The Stability and Thermal Conductivity of Polyvinyl Ether-Based Nanolubricant - Safril Safril; Edwin Sahrial Solih; Ridho Hans Gurning; Adinda Rahmah Shalihah; Abdul Wahid Arohman (G-Tech: Jurnal Teknologi Terapan, 2026)
Heat transfer efficiency in lubrication systems can be achieved by utilising nanolubricants by dispersing nanoparticle additives into pure lubricants to increase nanolubricant stability and thermal conductivity. This study aims to investigate the effect of silicon dioxide (SiO₂) nanoparticle dispersion in polyvinyl ether (PVE)-based lubricants on the stability and thermal conductivity characteristics of nanolubricants. SiO₂/PVE nanolubricant was prepared using a two-step method with a volume concentration of 0.007%. Stability evaluation was carried out through UV–Vis spectrophotometry testing over a period of 30 days. Thermal conductivity was measured using KD2-Pro at a temperature range of 30 ℃ to 80 ℃. The results of the study showed that SiO₂/PVE was declared stable after 144 hours with an absorbance of 80%. Thermal conductivity characteristics decreased with increasing temperature, and the nanolubricant increased compared to PVE lubricants. The maximum increase in thermal conductivity was 2.72% compared to the pure lubricant, and at a test temperature of 30 °C, SiO₂/PVE was compared to SiO₂/corn oil, SiO₂/paraffin oil, SiO₂/sunflower SiO₂/oil, and SiO₂/soybean oil; the results showed an increase in thermal conductivity of 66.69%, 80.63%, 67.70%, and 46.45%, respectively. The thermal conductivity behaviour tends to increase when SiO₂ nanoparticles are dispersed into the pure lubricant, compared to the pure PVE lubricant and previous studies. These findings indicate that SiO₂/PVE nanolubricant produces a significant increase in thermal conductivity, resulting in accelerated heat transfer, reduced friction and wear, and ultimately leading to increased energy efficiency and improved overall system performance.